Rate capability and electrolyte concentration: Tuning MnO2 supercapacitor electrodes through electrodeposition parameters - Hamed Soltani; Hamed Bahiraei; Shahnaz Ghasemi; Mazdak Hashempour (Heliyon)
Manganese dioxide (MnO2) is a well-known pseudocapacitive material that has been extensively studied and highly regarded, especially in supercapacitors, due to its remarkable surface redox behavior, leading to a high specific capacitance. However, its full potential is impeded by inherent characteristics such as its low electrical conductivity, dense morphology, and hindered ionic diffusion, resulting in limited rate capability in supercapacitors. Addressing this issue often requires complicated strategies and procedures, such as designing sophisticated composite architectures. This study introduces a straightforward and cost-effective approach to tune and enhance the rate capability of MnO2 pseudocapacitor electrodes fabricated via the electrodeposition method. Among the electrodeposition parameters, the deposition time and electrolyte concentration, which influence the mass loading, electrode thickness, microstructure, and electrochemical properties, were the primary focus. Various electrodes were prepared potentiostatically in a two-electrode cathodic electrodeposition setup on a Ni foam substrate in a KMnO4 aqueous electrolyte, with bath concentrations (in terms of Mn ion) of 0.01 and 0.1 M, and electrodeposition times ranging from 1 to 15 min. Optimal rate capabilities were achieved at low bath concentrations and deposition times, primarily due to the structural properties of electrodes prepared under such circumstances. While electrodeposition at a 0.1 M electrolyte concentration resulted in the formation of electrolytic MnO2 with high supercapacitive rate sensitivity, reducing the bath concentration to 0.01 M primarily led to the formation of birnessite δ-MnO2, capable of maintaining a reasonable specific capacitance in the range of approximately 90–100 Fg–1 with almost no sensitivity to the charging/discharging rate, as confirmed by galvanostatic charge-discharge (1–10 Ag–1) and cyclic voltammetry (10–100 mVs−1) examinations. Along with the positive structural impacts of the layered birnessite with large interlayer spacing, the porous morphology (vertically aligned two-dimensional interconnected columns) and low thickness (≈2 μm) of the electrode prepared at the lowest bath concentration and electrodeposition time (0.01 M in 1 min electrode) contributed to its fast ionic diffusion kinetics for pseudocapacitive charge storage and the consequent high rate capability.